Transcription Factor Elf3 Modulates Vasopressin-Induced Aquaporin-2 Gene Expression in Kidney Collecting Duct Cells - Lin, Shu-Ting; Ma, Chia-Ching; Kuo, Kuang-Ting; Su, Yin-Fang; Wang, Wei-Ling; Chan, Tzu-Hsien; Su, Shih-Han; Weng, Shih-Che; Yang, Chian-Huei; Lin, Shuei-Liong; Yu, Ming-Jiun (Frontiers in Physiology, 2019)
Aquaporin-2 (AQP2) is a molecular water channel protein responsible for water reabsorption by the kidney collecting ducts. Many water balance disorders are associated with defects in AQP2 gene expression regulated by the peptide hormone vasopressin. Here, we studied roles of Elf3 (E26 transformation-specific (Ets)-related transcription factor 3) in AQP2 gene expression in the collecting duct cells (mpkCCD). Vasopressin increased AQP2 mRNA and protein levels without affecting AQP2 mRNA degradation, indicative of transcriptional regulation. Elf3 knockdown and overexpression respectively reduced and increased AQP2 gene expression under basal and vasopressin-stimulated conditions. However, the vasopressin-to-basal ratios of AQP2 gene expression levels remained constant, indicating that Elf3 does not directly mediate vasopressin response but modulates the level of AQP2 gene expression inducible by vasopressin. The Elf3-modulated AQP2 gene expression was associated with AQP2 promoter activity, in line with Elf3’s ability to bind an Ets element in the AQP2 promoter. Mutation in the Ets element reduced both basal and vasopressin-stimulated AQP2 promoter activity, again without affecting vasopressin-to-basal ratios of the AQP2 promoter activity. Lithium chloride reduced both Elf3 and AQP2 mRNA in the mpkCCD cells as well as in mouse kidney inner medulla. We conclude that Elf3 modulates AQP2 promoter activity thereby gauging vasopressin-inducible AQP2 gene expression levels. Our data provide a potential explanation to lithium-induced nephrogenic diabetes insipidus where lithium reduces Elf3 and hence AQP2 abundance.